2020
DOI: 10.1002/ange.202003676
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Peptide Synthesis Enabled by a Transient Protecting Group

Abstract: The growing interest in synthetic peptides has prompted the development of viable methods for their sustainable production. Currently, large amounts of toxic solvents are required for peptide assembly from protected building blocks, and switching to water as a reaction medium remains a major hurdle in peptide chemistry. We report an aqueous solid‐phase peptide synthesis strategy that is based on a water‐compatible 2,7‐disulfo‐9‐fluorenylmethoxycarbonyl (Smoc) protecting group. This approach enables peptide ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…It is important to mention that N α -Smoc building blocks D, N, Q, R, Y possessed unprotected side chains. 20 High-performance liquid chromatography (HPLC) traces of crude peptides, shown at Figure 3, clearly demonstrate that all constructs were assembled in sufficient purity and good yield (see also Section 2). Electrospray ionization mass spectrometry (ESI-MS) analysis revealed that the observed mz signals corresponded to the calculated ones.…”
Section: Applicationmentioning
confidence: 83%
See 2 more Smart Citations
“…It is important to mention that N α -Smoc building blocks D, N, Q, R, Y possessed unprotected side chains. 20 High-performance liquid chromatography (HPLC) traces of crude peptides, shown at Figure 3, clearly demonstrate that all constructs were assembled in sufficient purity and good yield (see also Section 2). Electrospray ionization mass spectrometry (ESI-MS) analysis revealed that the observed mz signals corresponded to the calculated ones.…”
Section: Applicationmentioning
confidence: 83%
“…18,19 In our earlier paper, we have described a sulfonated version of an Fmoc protecting group, 2,7-disulfo-9-fluorenylmethoxycarbonyl (Smoc), that allowed SPPS under aqueous conditions as well as efficient postsynthetic purification of the peptides. 20 Thus, we have established a concept for efficient aqueous solid-phase peptide synthesis (ASPPS) and optimized it in view of coupling efficiency and N-terminal deprotection conditions. However, the majority of current solid supports and linker systems are not suitable for SPPS under aqueous conditions.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hopefully, SPPS is already experiencing a smooth transition to greener chemistries, 64 which include the use of water as the solvent for the concatenation of amino acids. 65 Post Another trend, which is critical to the discovery of small protein therapeutics, is the development of fast methods for the production of synthetic protein libraries. The development of fast synthesis techniques will enable full benefit from the high throughput methods that are available for screening small molecules.…”
Section: Conclusion and Perspective Commentmentioning
confidence: 99%
“…There is great interest in reducing the environmental impact of organic solvents used in synthetic reactions, in peptide synthesis, and other fields. Many approaches to cleaner peptide synthesis have been investigated. Recently, the Fmoc group has been modified with sulfonic acid groups to confer water solubility, hence enabling sustainable green synthesis of peptides in aqueous media. , This follows on from Merrifield’s original development of monosulfated 2-sulfo-9-fluorenylmethyloxycarbonyl chloride amino acids for peptide purification . A range of amino acids linked to the 2,7-disulfo-9-fluorenylmethoxycarbonyl (Smoc) group (Scheme ) is now commercially available.…”
Section: Introductionmentioning
confidence: 99%